(untitled) (Comparative Professional Pedagogy, 2024)
The article is dedicated to revealing the features of interprofessional education (IPE) for pharmacists in the experience of Great Britain. It is established that interprofessional education began to integrate into the educational system of the United Kingdom in response to the growing need for coordination of medical services and the improvement of the quality of healthcare. It is stated that the Centre for the Advancement of Interprofessional Education (CAIPE) defines interprofessional education as "a process where two or more professions in health or social care learn interactively with the common goal of providing effective collaboration and improving health outcomes for patients." It is found that at least two-thirds of the UK universities include IPE in their educational programs. Successful IPE programs are presented as a part of pharmaceutical programs at the UK universities; their positive impact on the professional development of future pharmacists and the improvement of healthcare quality is proved. It is established that the main elements of such programs are joint lectures, simulation exercises, and group projects that contribute to developing teamwork and communication skills. Great attention is paid to developing key competencies for effective interprofessional collaborative practice and collaboration in multidisciplinary teams in the IPE of pharmacists. In the process of the research, it is found out that various methods of professional training were adopted and adapted for interprofessional education: active, interactive, reflective and patient-oriented. It is stated that among the methods of developing IPE competencies for pharmacy students are problem-based learning, observational learning, laboratory simulation-based learning, case-based learning, workshops, and e-learning. These methods help pharmacy students to develop their communication skills, teamwork, leadership, and ethical practice. It is concluded that the integration of IPE into the curricula of medical higher education institutions contributes to the formation of qualified and comprehensively prepared specialists in the field of healthcare.